Biomedical Waste Management: An Assessment of Knowledge, Attitude and Practice among Healthcare Workers in Tertiary Care Hospital, Chhattisgarh - Trinjana Diwan; Kamlesh Jain; Neha Singh; Nirmal Verma; Vineet Jain (Journal of Pure and Applied Microbiology, 2023)
In the current scenario, medical concern is fundamental for everyone’s existence in addition to well-being, but the waste produced as of healthcare facilities signifies an actual concern in our surroundings. One of the healthcare workers (HCWs) most crucial duties is to handle biomedical waste (BMW) created in a healthcare institution properly since inappropriate management of BMW not only puts both individuals and the environment at risk but might also lead to lawful act opposed to healthcare workers and hospital authority. Current research plan is intended to assess biomedical waste management in a tertiary care hospital in Raipur, Chhattisgarh. A facility-based cross-sectional observational study was conducted at Dr. Bhimrao Ambedkar Memorial Hospital, Raipur; Chhattisgarh from July 2021 to August 2021. Assessment of knowledge, attitude, and observation was done by interviewing 105 healthcare workers, selected by simple random sampling, using a predesigned, semi-structured questionnaire. The analysis revealed that medical staff had good knowledge, attitude and practice of biomedical waste management than the paramedical professionals or non-medical workers. There is an imperative need for orientation training to protect themselves, and citizens visiting this healthcare facility and close by communities.